Successful antiretroviral therapy by using unusual antiretroviral combinations in heavily pre-treated patients: two case reports. (October 2015) - Taramasso, Lucia; Dentone, Chiara; Alessandrini, Anna; Bruzzone, Bianca; Icardi, Giancarlo; Garraffo, Rodolphe; De Macina, Ilaria; Viscoli, Claudio; Di Biagio, Antonio; ,
In the context of HIV-infected patients with several past antiretroviral therapies and multiple failures, it is possible to be faced with viruses resistant to all drug classes. We report on two HIV-1 infected patients in which the historical genotype showed mutations against all the major drug classes and in which viral suppression has been obtained by non-conventional antiretroviral therapy regimens, including the combination of darunavir at high dosage (800 mg bid), dolutegravir (50 mg bid) and a third agent, i.e. enfuvirtide in the first case and etravirine in the second one.